Development of limiting dilution viability pcr method to assess the effectiveness of selected biocides to treat indoor fungi growth - Er, Ching Ming (2019)
Indoor fungal contamination should be treated with cost-effective and green methods. Biocides have direct biological effect on living organisms but the evidence on their control of indoor fungal contamination is scarce. Using conventional cultivation to evaluate their effectiveness is time consuming while polymerase chain reaction (PCR) provides a fast and reliable alternative. The incorporation of serial dilution technique and viability information in PCR has made it suitable to evaluate the effectiveness of biocides. Thus, this study aimed to assess the antifungal ability of biocides, zinc salicylate (ZS), calcium benzoate (CB) and potassium sorbate (KS) to treat indoor fungal contamination through developing limiting dilution viability PCR (vPCR). These biocides were selected as they successfully controlled the growth of indoor waterborne fungi previously. Indoor air sampling revealed that higher educational building of computer studies (Building A) and of civil engineering studies (Building B) were contaminated by 509 CFU/m3 and 805.7 CFU/m3 of indoor airborne fungi, respectively. Two indoor fungi, Talaromyces spp. and Aspergillus niger were identified. They were subjected to biocides-treatment and subsequent conventional cultivation and limiting dilution vPCR due to their potential risks against humans’ health. The limiting dilution vPCR was developed by incorporating the pre-treatment of propidium monoazide (PMA) before deoxyribonucleic acid (DNA) extraction and the serial dilution of the DNA template in PCR. This approach was proven to effectively enumerate the effectiveness of biocides to treat indoor fungi. KS was shown to have the best effectiveness (100%) to prevent the growth of Talaromyces spp, followed by ZS (80.8%) and CB (no effect). KS also showed the best effectiveness against A. niger (100%) at the early stage of the study but its effect reduced with time. ZS showed durable effect (66.67%) against A. niger Day 9 cultures. Inconstant results were indicated by cultivation method. This study has provided a cheaper, more accurate and suitable approach to determine the effectiveness of treatment of indoor fungi than cultivation methods.